Pengembangan Lembar kerja peserta didik Berdasarkan Konsep Mind mapping Dengan Menerapkan Metode Debat Aktif Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X SMK Bhakti Kencana Mataram pada Materi Stoikiometri Tahun Pelajaran 2020/ 2021 - Listari, Nening (Jurnal Ilmiah IKIP Mataram, 2020)
This research aims to determine the increase in student learning outcomes using student worksheets based on the concept of mind mapping applied in the active debate learning method. The population in this study amounted to 33 people while the sample used was 15 people. The development method used in this research is the Dick and Carey method, the development steps are: 1) Identification of objectives; 2) conduct a learning analysis; 3) Identify the behavior and characteristics of students, 4) Formulate performance objectives; 5) Develop assessment instruments; 6) Developing a learning strategy; 7) Designing and implementing performance evaluation; 8) Designing and implementing Formative Evaluation; 9) Revising learning materials. This Student Worksheet is tested through formative evaluation. Formative evaluation results data in the form of suggestions, responses from trial subjects are used as input to revise and improve the Student Worksheets. Based on the results of data analysis in the form of calculations using the linkert scale to test feasibility, getting a score of 77.6 which is categorized as feasible and the calculation using the presentation formula to analyze the increase in learning outcomes with a comparison of 34% pre-test while 41% post-test proved an increase in learning outcomes. students so that Student Worksheets Based on the Mind Mapping concept it has been proven to improve learning outcomes and is feasible to use.